H1-Receptor activation triggers the endogenous nitric oxide signalling system in the rat submandibular gland - Enri Borda; Graciela Stranieri; Leonor Sterin-Borda (Mediators of Inflammation)
Background: Histamine is released from mast cells by immunologic and non-immunologic stimuli during salivary gland inflammation, regulating salivary secretion. The receptor-secretory mechanism has not been studied in detail.